2006
DOI: 10.1002/cne.20924
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic connections of the auditory cortex in marmoset monkeys: Core and medial belt regions

Abstract: In this study and its companion, the cortical and subcortical connections of the medial belt region of marmoset monkey auditory cortex were compared with the core region. The main objective was to document anatomical features that account for functional differences observed between areas. Injections of retrograde and bi-directional anatomical tracers targeted two core areas (A1 and R), and two medial belt areas (RM, rostromedial; CM, caudomedial). Topographically distinct patterns of connections were revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
133
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 193 publications
(156 citation statements)
references
References 75 publications
21
133
1
1
Order By: Relevance
“…These areas are interconnected densely with neighboring core and belt regions, but avoid the parabelt. Their principal thalamic input is from the medial geniculate body ventral division (de la Mothe et al, 2006). In the cat, the tonotopic areas AI, AAF, P, VP, Ve are heavily interconnected, but unlike the monkey, also receive minor multisensory and limbic projections (present results).…”
Section: Divergent Input-sparse Divergent Corticocortical Projectionssupporting
confidence: 52%
See 1 more Smart Citation
“…These areas are interconnected densely with neighboring core and belt regions, but avoid the parabelt. Their principal thalamic input is from the medial geniculate body ventral division (de la Mothe et al, 2006). In the cat, the tonotopic areas AI, AAF, P, VP, Ve are heavily interconnected, but unlike the monkey, also receive minor multisensory and limbic projections (present results).…”
Section: Divergent Input-sparse Divergent Corticocortical Projectionssupporting
confidence: 52%
“…Their principal thalamic input is from the dorsal and medial nuclei of the medial geniculate body (MGd, MGm, SG, Lim) (Hackett et al, 1998;de la Mothe et al, 2006), and these areas are heavily connected with adjacent cortical core and belt areas. The cat non-tonotopic regions (AII, DZ, AES) share many of the same types of thalamic (Lee and Winer, 2008a) and cortical connections (Fig.…”
Section: Divergent Input-sparse Divergent Corticocortical Projectionsmentioning
confidence: 99%
“…Other studies have shown that CM is tonotopically organized, and that response latencies are as short as, or shorter than, neurons in A1 (Bieser et al, 1996;Lakatos et al, 2005). A potential anatomical explanation for these features is that the principal thalamic input to CM derives from the rostral pole of the MGC, and perhaps MGv, as well (de la Mothe et al, 2006b;. In cats, neurons in the rostral pole, which has strong connections to AAF, are tonotopically organized and have short response latencies comparable to MGv (Imig et al, 1984;Imig et al, 1985;Lee et al, 2005;Lee et al, 2004;Morel et al, 1987).…”
Section: The Role Of CM In Auditory Cortical Processingmentioning
confidence: 98%
“…nar, have been shown to project to the auditory belt and parabelt areas (Fitzpatrick and Imig, 1978;Morel and Kaas, 1992;Pandya et al, 1994;Hackett et al, 1998b;de la Mothe et al, 2006) [also see Budinger et al (2006) for a study in the gerbil]. All of these structures are responsive to visual stimulation.…”
Section: Pathways Of Multisensory Enhancement Of Auditory Cortexmentioning
confidence: 99%